Semantic Web programming - Hebeler, John (Wiley India, 2009)
"The Semantic Web offers a revolutionary and powerful way to build intelligent software applications that take advantage of the information and services that exist on the Web, as well as within the enterprise. The Semantic Web delivers on the promise of "Web 3.0" - facilitating automated data integration, processing, and reasoning." "This author team of Semantic Web professionals shows how to apply Semantic Web technologies to build practical, real-world applications and to solve real-world problems. The authors provide a generous supply of working code examples showing how to put concepts into practice."--BOOK JACKET.